Biblical Names in Cuban Anthroponomastic Studies: Results and Perspectives: Los nombres bíblicos en los estudios antroponomásticos cubanos: resultados y perspectivas - Campo Yumar, Luis Ramón (Onomástica desde América Latina, 2024)
Denominations associated with religion have been the least studied within the panorama of Cuban studies on first names. The few investigations on this subject have focused more on the use of the Catholic saints’ names than on the vitality and permanence of names linked to the Bible. The objective of this article is to describe bibliographically, theoretically and methodologically certain aspects of the presence of biblical names in the research on first names in Cuba. The present study is structured as follows: 1) first, an overview of the main anthroponomastic researches that address the religious theme in Cuba (Sánchez et al.,1985; Rosales, 2009; Rabelo, 2020; Campo, 2020, among others) and their characteristics are offered; 2) next, two theoretical perspectives are put forward to analyze biblical names: a formal one, understanding the Bible as a multilingual onomastic inventory; and a motivational one, which is interested in the biblical concept as a reason for selection. From the interaction between both criteria arises the concept of biblicality associated to finished characteristics of the names that evidence with different degrees of accuracy their formal or motivational relation with the Bible; also 3) analyses of biblical names are offered (or outlined) from several perspectives (orthographic, motivational, statistical, biblical) using data, both from elaborated corpora (beginning of XXI century) and offered by previous Cuban researches (between 1980 and 2020). As support for the research, various sources and resources currently available in Cuba are used (or proposed to be used), such as: official documents, telephone guides and records, interviews with carriers, among others; 4) finally, aspects of the study are highlighted in some brief final considerations. In view of the bibliographic review carried out, this is the first article dedicated solely to the study of biblical names in Cuba from the anthroponomastic perspective.